1999
DOI: 10.1046/j.1432-1327.1999.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

An ethanol‐inducible MDR ethanol dehydrogenase/acetaldehyde reductase in Escherichia coli

Abstract: An ethanol-active medium-chain dehydrogenase/reductase (MDR) alcohol dehydrogenase was isolated and characterized from Escherichia coli. It is distinct from the fermentative alcohol dehydrogenase and the class III MDR alcohol dehydrogenase, both already known in E. coli. Instead, it is reminiscent of the MDR liver enzyme forms found in vertebrates and has a K m for ethanol of 0.7 mm, similar to that of the class I enzyme in humans, however, it has a very high k cat , 4050 min 21 . It is also inhibited by pyraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 34 publications
(59 reference statements)
2
27
0
Order By: Relevance
“…Therefore, we measured the enzymatic activity of pAdhP and found 108 and 126 U* min −1 * mg −1 for ethanol and propanol substrates, respectively. These values are in the range of reported activities for alcohol dehydrogenase enzymes from various species [unit: U* min −1 * mg −1 ]: 43 for E. coli, 40-184 for Drosophila melanogaster and 210-7300 for Saccharomyces cerevisiae (Shafqat et al 1999, Blandino et al 1997, Bozcuk et al 2004. Therefore, we concluded that the recombinant protein was active and that its spatial conformation corresponded to that of the native protein.…”
Section: Adhp Effect On Senpssupporting
confidence: 57%
“…Therefore, we measured the enzymatic activity of pAdhP and found 108 and 126 U* min −1 * mg −1 for ethanol and propanol substrates, respectively. These values are in the range of reported activities for alcohol dehydrogenase enzymes from various species [unit: U* min −1 * mg −1 ]: 43 for E. coli, 40-184 for Drosophila melanogaster and 210-7300 for Saccharomyces cerevisiae (Shafqat et al 1999, Blandino et al 1997, Bozcuk et al 2004. Therefore, we concluded that the recombinant protein was active and that its spatial conformation corresponded to that of the native protein.…”
Section: Adhp Effect On Senpssupporting
confidence: 57%
“…The responsible enzyme turned out to be AdhP, a little-known alcohol dehydrogenase, present in both S. enterica and E. coli, that is known to be induced by ethanol (42). Mutations in this gene were tested because they had previously been seen to contribute to ethanolamine metabolism in certain mutant strains (T. Fazzio, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…Further selection using up to 500 mM allyl alcohol failed to yield additional mutants. We also tested a strain with a deletion of the adhP alcohol dehydrogenase (31), but this deletion did not affect ethanol production significantly during glucose fermentation by E. coli ZH88. Effect of yeast extract and pH on coproduction of acetaldehyde and hydrogen.…”
mentioning
confidence: 99%